Biomarkers in Exhaled Breath Condensate and Serum of Chronic Obstructive Pulmonary Disease and Non-Small-Cell Lung Cancer. (1st August 2013) - Lim, Mann Ying; Thomas, Paul S.
Abstract : Chronic obstructive pulmonary disease (COPD) and lung cancer are leading causes of deaths worldwide which are associated with chronic inflammation and oxidative stress. Lung cancer, in particular, has a very high mortality rate due to the characteristically late diagnosis. As such, identification of novel biomarkers which allow for early diagnosis of these diseases could improve outcome and survival rate. Markers of oxidative stress in exhaled breath condensate (EBC) are examples of potential diagnostic markers for both COPD and non-small-cell lung cancer (NSCLC). They may even be useful in monitoring treatment response. In the serum, S100A8, S100A9, and S100A12 of the S100 proteins are proinflammatory markers. They have been indicated in several inflammatory diseases and cancers including secondary metastasis into the lung. It is highly likely that they not only have the potential to be diagnostic biomarkers for NSCLC but also prognostic indicators and therapeutic targets.